Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia - Celis, Liliana V.; Feijoo, Alexander; Rangel-Ch., Orlando (Zootaxa, 2018)
Two new earthworm species from grassland and herbaceous plant formations in the departments of Arauca y Casanare (Orinoquian region of Colombia) are described, Righiodrilus cusiani sp. nov. (Glossoscolecidae) and Andiodrilus cravijae sp. nov. (Rhinodrilidae). Righiodrilus cusiani sp. nov. is close to R. arapaco (Righi, 1982) in the position of the clitellum, but differs in the extension of the tubercula pubertatis, the extension of the seminal vesicles and the position of the male pores. Andiodrilus cravijae sp. nov. is close to A. major Michaelsen, 1900 in the position of the clitellum and the spermathecal pores, but is different in the extension of the tubercula pubertatis and in the position of the male and female pores.